Mapeamento das ações ambientais no âmbito dos Territórios da Cidadania de Sergipe - Omena, André Luiz Rodrigues de Albuquerque (2019)
achieving sustainable regional development and guaranteeing social rights. Focused on the poorest regions of the country, it is based on the integration between the three governmental spheres and society, through the construction of a Territorial Plan for Sustainable Rural Development (PTDRS). The state of Sergipe has four Territories of Citizenship (Alto Sertão, Baixo São Francisco, Sertão Occidental and Sergipano South). However, there is a lack of data that could reveal the results achieved by the program at the state level, especially with regard to the contribution in the environmental sphere, with a view to a sustainable development model of rural development. In view of this reality, it was intended to assess to what extent the environmental dimension is contemplated in the PTDRS of the Sergipe Citizenship Territories. The qualitative and quantitative research adopted the exploratory approach and was based on the information obtained from the interviews with representatives of the Territorial Colleges, participant observation, program execution reports and the literature used as reference for the study. The data obtained allow us to affirm that the environmental question poses a great challenge for the actions developed in the Citizenship Territories of Sergipe to be established on a sustainable basis, just as the program prescribes. In spite of the advances achieved in the social management of the territory, through the empowerment and active participation of society, both in debates and proposals, the mechanisms of control of environmental actions by civil society in the Citizenship Territories of Sergipe still lack with more qualified interventions.